Establishing Referral Laboratory Testing Governance and Addressing "Miscellaneous" Test Orders across an Academic Health System - Chambliss, Allison B; Deignan, Joshua L; Isip, Charlemagne; Trinh, Monique; Werre, William; Ziman, Alyssa (The journal of applied laboratory medicine, 2025)
Referral (send-out) laboratories support clinical needs but may cause issues for hospitals or health systems related to regulations and governance, specimen logistics, test result availability, and cost and reimbursement. The use of a "miscellaneous" referral test order can increase risks of specimen collection or processing errors, result delays, and repeat testing. We established an approved referral laboratory test list and a digital form for providers to request new referral tests. We collated laboratory stewardship committee decisions over a 20-month period. Separately, we retrospectively reviewed referral tests ordered as miscellaneous across our health system over 1 year. Subject matter experts identified appropriate tests to build as discretely orderable in the electronic health record. Following targeted provider notification of the new tests, we assessed their uptake and impact on result turnaround times for the first 5 built tests over 6 months. Our laboratory stewardship committee approved 16 of 27 provider requests to build new referral tests over the first 20 months following implementation of the new request process. In addition, 37 of the 100 most frequently ordered miscellaneous tests were recommended to be built as discrete orders. Uptake of the first 5 built tests (relative to providers continuing to use miscellaneous orders) averaged 64% over the first 6 months. Result turnaround times improved by an average of 1.1 days when the discrete orders were used. We successfully established oversight of referral laboratory testing across our health system, pivoted orders away from miscellaneous, and observed improvements in turnaround times.